Opening Speech Hot Chocolate Research Talk siri 1/2025 Advancing Impactful Research: unleashing opportunities with asea-uninet grant recipients /Prof Dr Mohamad Hafiz Mamat Deputy Rector Research and Innovation - Mamat, Mohamad Hafiz (2025)
This Hot Chocolate Research Talk Siri is an annual event led by Research & Innovation Department UCS that provides platform for 5 researchers to collaborate and synergize in specialized fields and establishing joint research facilities with external parties.